Essential Oil of the Leaves of Arum Conophalloides (Araceae) From Iran: Essential Oil of Arum Conophalloides - Hamed Haghighi, (Iranian Journal of Pharmaceutical Sciences, 2016)
The leaves of Arum conophalloides (Araceae) were used in some west areas of Iran as a dessert. The aerial parts of the herb were collected from Sahneh Mountains, Kermanshah Province, west of Iran and was hydrodistilled by Clevenger-type apparatus. Composition of the essential oil was determined by GC and GC/MS. Totally, 18 components (92% of total essential oil) were identified. The oil contains mainlyΤ-muurolol (%25.4), Ionone (%12.6), nonanal (%17.7), Τ-cadinol (%8.9), Fitone (%7.9), and Methyl palmitate (%7.0). The chemical composition of essential oils from the herbs is being reported for the first time.